L-Fuzzy Fixed Points Theorems for L-Fuzzy Mappings via βℱL-Admissible Pair - Maliha Rashid; Akbar Azam; Nayyar Mehmood (The Scientific World Journal)
We define the concept of βℱL-admissible for a pair of L-fuzzy mappings and establish the existence of common L-fuzzy fixed point theorem. Our result generalizes some useful results in the literature. We provide an example to support our result.